Diabetic Ketoacidosis as Presenting Feature of Acromegaly (KYAMC Journal, 2026)
A 50-year-old man's initial symptom of acromegaly was diabetic ketoacidosis (DKA). The patient presented with abdominal pain, polyuria, polydipsia, hyperhidrosis, and enlargement of the extremities. His acromegalic features also were macroglossia, and jaw prominence. Lab testing showed hyperglycemia, high HbA1c, and elevated IGF-1. MRI showed a  pituitary macroadenoma. After initial treatment following the diabetic ketoacidosis protocol, he was referred to neurosurgeon. DKA is often the presenting feature of type 1 diabetes. It may also occur in type 1 and type 2 diabetes due to severe illness, infections, myocardial infarction, heart failure, pancreatitis, pregnancy, or steroids. In acromegaly, GH induces insulin resistance and poor glucose metabolism. Acromegaly may induce glucose intolerance, however, DKA is rare. Some cases were treated with surgery or somatostatin. This case highlights the need to treat acromegaly in unexplained DKA patients, particularly those with physical symptoms.